Pancreaticoduodenectomy preserving aberrant gastroduodenal artery utilized in a previous coronary artery bypass grafting: A case report and review of literature. Issue 48 (3rd December 2021) - Toda, Takeo; Kanemoto, Hideyuki; Tokuda, Satoshi; Takagi, Akihiko; Oba, Noriyuki
Abstract: Rationale: Pancreaticoduodenectomy (PD) is a technically demanding procedure with high rates of morbidity and mortality. Therefore, preoperative evaluation of anatomy is indispensable. Multi-detector row computed tomography (CT) enables us to precisely understand arterial anatomy. It is a well-known fact that anatomical variants are often present in the hepatic artery (HA) but rarely in the gastroduodenal artery (GDA). We present the case of a patient with ampullary cancer with a rare anatomical anomaly, "replaced GDA (rGDA) " arising from the superior mesenteric artery, along with a history of coronary artery bypass grafting (CABG) using right gastroepiploic artery (RGEA). Patient concerns: A 69-year-old male patient was referred to our department for further investigation of elevated hepatobiliary enzymes. He presented with no symptoms besides intermittent fever of 38°C. He had an operative history of CABG using the RGEA. Diagnosis: Abdominal CT and esophagogastroduodenoscopy showed an ampullary tumor and biopsy specimen from the lesion revealed adenocarcinoma. CT angiography revealed the rGDA instead of a normal common HA. Intervention: We performed a safe PD, preserving the rGDA and the RGEA to maintain hepatic and cardiac perfusion. Outcomes: Owing to the presence of a refractory pancreatic fistula, the length-of-hospital stay was extended, and he was discharged on postoperative day 72 without vascular complications. At present, the patient is in good physical condition and does not present with cardiovascular complications as well as tumor recurrence at 6 months after surgery. Lessons: This is possibly the first case of a patient who underwent PD and has a proper HA following a GDA arising from a superior mesenteric artery (rGDA) and has a previous operative history of CABG using the gastroepiploic artery. The coexistence of the history of cardiovascular surgery made PD for this patient considerably more challenging. In the case of a rare anatomical anomaly, a coronary artery bypass via the RGEA should not be considered as an obstacle when R0 resection is achievable.